Development of the Late Paleozoic, Mesozoic and Cenozoic sedimentary succession in SW Barents Sea and their role in fluid leakage process - Hassan, Syed Yasir (Universitetet i Tromsø, 2012)
2D seismic and well data have been used to understand the geological evolution of the SW Barents Sea by interpreting different seismic units and to evaluate their role in distribution of fluid migration system. Eight seismic unit including seafloor are identified in the study area based on well tie with seismic data. Torsk and Kolmule formation show western progradational pattern suggesting deposition during relative sea level fall. Stappen High and Loppa High appear to act as main sediment source area in western margin of SW Barents Sea. The distributions of fluid flow features are significantly higher in western part than in the eastern part of study area. The distribution of fluid flow show direct relationship with structural elements of SW Barents Sea although net erosion might have had added effect on fluid migration process. The late Jurassic Hekkingen formation, are considered as the widespread source rock in western Barents Sea. In addition to this, lower Cretaceous unit and Snadd formation are potential source rock in the study area. Among the various observed fluid flow features were gas chimneys, leakage along faults and high amplitude anomalies. Gas chimneys were most abundant fluid flow features in the study area. The location of chimney structures are associated with major fault complexes in the study area suggesting close relation between the fault and fractures. The inferred gas leakages are closely related to the Cenozoic evolution of the Barents Sea, and are possible caused by gas expansion due to removal of overburden of sediments from the Barents Sea.